Stability enhancement of Al2O3, ZnO, and TiO2 binary nanofluids for heat transfer applications - Ans Ahmed Memon (21633692) (2024)
Primary goal of this research is to enhance stability of nanofluids which is vital for maintaining consistent thermophysical properties during various applications. Nanofluid stability is essential for obtaining the uniform thermophysical properties during its application. X-ray diffraction and zeta potential were performed to characterize three nanoparticles, namely TiO2, Al2O3, and ZnO. Experimental work was carried out under several trials to enhance the stability of nanofluids. Initially, deionized water was used as base fluid for stability analysis, but nanoparticles agglomerate within after 5 h. Second, alkaline water was selected as base fluid at different pHs ranging from 7 to 14 to analyze the stability of the nanofluids. Finally, the effect of surfactant addition on the stability of prepared nanofluids was also investigated. Observations revealed that at pH 11, nanoparticles exhibited enhanced stability compared to other pH levels. This stability can be attributed to the high zeta potential, fostering electrostatic repulsion between individual particles. It was concluded from the results that zeta potential increases in cases of (TiO2 + ZnO) and (Al2O3 + ZnO) from −44.2 to −47.8 mV and −42.4 to −44.1 mV with the addition of surfactant, respectively. In the case of (Al2O3 + TiO2), zeta potential decreases slightly from −47.7 to −44.9 mV with the addition of surfactant. Other Information Published in: Open Physics License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/phys-2023-0199